Penerapan Metode AHP-TOPSIS Dalam Pemilihan Siswa Berprestasi Di SMAN 1 Dumai - Suri, Melati Rahma; Nurcahyo, Gunadi Widi; Hendrik, Billy (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
The system used by schools in selecting outstanding students is still calculated manually, making it prone to errors in calculating the selection of outstanding students. Therefore, a new system is needed, namely a decision support system for selecting outstanding students. The aim of this research is to produce a system for determining students who have the right to enter superior classes. In this study, data from 73 grade 11 students was used using the AHP-TOPSIS combination method. In this research, there are two additional criteria, namely interview scores and psychological scores. The addition of these two criteria is because to enter the superior class you not only have to be outstanding but also have strong interpersonal skills. The results provided by testing 73 student data manually and system testing gave a difference of 24% for the superior class of Mathematics and Natural Sciences and 16% for the superior class of Social Sciences where there were 6 students in the Mathematics and Natural Sciences class and 4 students in the Social Sciences class who were entitled to enter the superior class. but there are no results provided by the old system. The differences produced by the new system and also two additional criteria are able to provide better results in determining outstanding students.